Taxation, non-tax revenue and democracy: New evidence using new cross-country data. (September 2018) - Prichard, Wilson; Salardi, Paola; Segal, Paul
Highlights: Employs improved data on the composition of government revenue to implement improved tests of the political resource curse. Evidence of a political resource curse across a wide range of econometric estimators, with large magnitude. Evidence that the political resource curse is driven by changes in government revenues rather than resource income. Evidence that natural resource wealth is anti-democratic, rather than stabilizing, in both autocracies and democracies. Evidence that the political resource curse is best understood as a long-term relationship. Abstract: A large body of econometric research has generated growing support for the existence of a political resource curse, but has nonetheless continued to be regularly punctuated by research contesting those conclusions. This continuing disagreement can be explained in significant part by problems associated with low-quality government revenue data: it has undermined the robustness of many existing findings, while leading other researchers to rely on alternative measures of resource income as their primary explanatory variable – a highly imperfect measures of the underlying relationship of interest. We re-examine the relationship between taxation, non-tax revenue and democracy by employing dramatically improved data developed specifically for this research. We find the strongest evidence to date of a political resource curse, and provide evidence about the specific details of the underlying relationship: (i) natural resource wealth is anti-democratic, rather than merely stabilizing; (ii) it is driven primarily by changes in the composition of government revenue; (iii) it is best understood as a long-term relationship, rather than short-term changes in resource wealth being quickly translated into major political changes; and (iv) it is driven primarily by oil wealth, rather than mineral wealth, because governments are comparatively effective at translating oil wealth into the government revenues that drive the political resource curse.